In situ electrochemical scanning/transmission electron microscopy of electrode–electrolyte interfaces. (September 2020) - Unocic, Raymond R.; Jungjohann, Katherine L.; Mehdi, B. Layla; Browning, Nigel D.; Wang, Chongmin
Abstract: Abstract : Insights into the dynamics of electrochemical processes are critically needed to improve our fundamental understanding of electron, charge, and mass transfer mechanisms and reaction kinetics that influence a broad range of applications, from the functionality of electrical energy-storage and conversion devices (e.g., batteries, fuel cells, and supercapacitors), to materials degradation issues (e.g., corrosion and oxidation), and materials synthesis (e.g., electrodeposition). To unravel these processes, in situ electrochemical scanning/transmission electron microscopy (ec-S/TEM) was developed to permit detailed site-specific characterization of evolving electrochemical processes that occur at electrode–electrolyte interfaces in their native electrolyte environment, in real time and at high-spatial resolution. This approach utilizes "closed-form" microfabricated electrochemical cells that couple the capability for quantitative electrochemical measurements with high spatial and temporal resolution imaging, spectroscopy, and diffraction. In this article, we review the state-of-the-art instrumentation for in situ ec-S/TEM and how this approach has resulted in new observations of electrochemical processes.